Detection of Secondary Metabolites in Cucumber (Cucumis sativus) Leaves and Its Potential as Candidates for Acne Drug Using Histochemical Analysis and In Silico Study - Asari, Devi Indrayani Fitri; Rafsanjani, Ramizard; Vikriansyah, Muchammad Faruq; Muzayyan, Abdullah Rozzen; Mubarakati, Nurul Jadid; Jayanti, Gatra Ervi (EXSACT-A, 2023)
Acne is a facial skin problem that is generally experienced by 75-80% of adolescents as a result of excessive production of oil glands and sweat, inflammatory mediators. The acnecausing bacteria, Propionibacterium acnes, involves KAS III and JNK 1 proteins, so it is expected to be an effective anti-inflammatory and antibacterial strategy. Cucumber leaves are known to have biological activity as a candidate for acne medication. This study aims to detect secondary metabolites in cucumber leaves through histochemical and in silico analysis. Histochemical analysis was carried out by preparing fresh leaves through lower leaf incisions by dropping secondary metabolite detection reagents and then observing the color changes microscopically. The in silico test aims to determine the physicochemical properties, pharmacokinetic properties and interactions of the active compounds with KAS III and JNK1 as acne drug targets through molecular docking. Histochemical analysis showed that cucumber leaves positively contained secondary metabolites, namely terpenoids, flavonoids, alkaloids, tannins, and phenols. Meanwhile, it was known that isovitexin, cucurbitacin B & C had fairly good physicochemical properties, but only isovitexin and cucurbitacin C had the best pharmacokinetic properties. Based on the results of molecular docking, there are the same amino acid bonds between isovitexin and the control at the JNK1 receptor, namely the amino acids Ile:32, Val:40 and Leu:168 and the binding affinity value is low so it is predicted to be the most effective in inhibiting JNK1. Therefore, cucumber leaves open up a new potential as a candidate for natural acne preparations.Keywords: acne, cucumber, secondary metabolites, histochemical, in silico